Efficacy and Safety of Oral Anticoagulants in Patients with Systolic Heart Failure in Sinus Rhythm: A Systematic Review and Meta-analysis of Randomized Controlled Trials and Cohort Studies - Nygaard, Marie H.; Hvas, Anne-Mette; Grove, Erik L. (TH Open, 2020)
Introduction There is conflicting evidence on the risk–benefit ratio of oral anticoagulants (OAC) in heart failure (HF) patients without atrial fibrillation. We aimed to evaluate the efficacy and safety of OAC in HF patients in sinus rhythm.Methods A systematic literature search was conducted using PubMed and Embase. We included randomized controlled trials (RCT) and cohort studies, comparing OAC with antiplatelet or no treatment/placebo in patients with HF. Outcomes evaluated were stroke, myocardial infarction (MI), all-cause mortality, and major bleeding.Results Five RCTs and three cohort studies were included. OAC was associated with a reduced risk of ischemic stroke when compared with no treatment/placebo (odds ratio [OR] = 0.67, 95% confidence interval [CI]: [0.47, 0.94]) and antiplatelet therapy (OR = 0.55, 95% CI: [0.37, 0.81]). No significant reduction was found in MI, when OAC was compared with no treatment/placebo (OR = 0.82, 95% CI: [0.63, 1.07]) or antiplatelet therapy (OR = 1.04, 95% CI: [0.60, 1.81]). The all-cause mortality analysis showed no significant reduction when comparing OAC with no treatment/placebo (OR = 0.99, 95% CI: [0.87, 1.12]) or antiplatelet therapy (OR = 1.00, 95% CI: [0.86, 1.16]). The nonsignificant effect of OAC on all-cause mortality was supported by a meta-analysis of the three cohort studies (OR = 1.02, 95% CI: [0.75, 1.38]). Patients treated with OAC had a significantly higher risk of major bleeding than patients receiving antiplatelet therapy (OR = 2.16, 95% CI: [1.55, 3.00]) and a numerically higher risk when compared with no treatment/placebo (OR = 2.38, 95% CI: [0.87, 6.49]).Conclusion The present study does not support the routine use of OAC in patients with HF in sinus rhythm.
Keywords: heart failure; oral anticoagulants; meta-analysis; sinus rhythm; warfarin; rivaroxaban